A week in the life of lung cancer survivors: Daily reports of stress, worry, mood, and symptoms. (October 2016) - Aronson, Keith R; Wagstaff, David A; Farace, Elana; Muscat, Joshua; Belani, Chandra; Almokadem, Salah; Fossum, Thyra
This study examined the day-to-day lives of early stage lung cancer survivors who were discharged from treatment between 2 and 24 months prior to the study. Lung cancer survivors were called on eight consecutive nights and completed an interview about their daily experiences. Repeated measures, multilevel analysis of the phone interview data was conducted. Survivors reported few daily stressor exposures or somatic symptoms. Daily moods were generally positive, and survivors reported living quite independently. Lung cancer survivors did not report experiencing health-related worry on a daily basis. The findings from this study create a much more positive picture of lung cancer survivorship relative to prior studies.